206k views
16 votes
I need help please, been stuck on this question.

I need help please, been stuck on this question.-example-1

1 Answer

3 votes

Answer:

D)
(1)/(6)

g¹(1) =
(1)/(6)

The inverse of the function
g(x) = \frac{x^{(1)/(3) }-1 }{2}

Explanation:

Step(i):-

Given that f(x) = (2x+1)³

Let y = (2x+1)³


y^{(1)/(3) } =2x+1


2x = y^{(1)/(3) } -1


x = \frac{y^{(1)/(3) }-1 }{2}

Step(ii):-

y = f(x) ⇒ x = f⁻¹ (y)


f^(-1) (y) = \frac{y^{(1)/(3) }-1 }{2}


f^(-1) (x) = \frac{x^{(1)/(3) }-1 }{2}

The inverse of the given function


g(x) = \frac{x^{(1)/(3) }-1 }{2}

Differentiating equation (i) with respective to 'x', we get


g^(l) (x) = (1)/(2) X (1)/(3) x^{(1)/(3) -1}


g^(l) (x) = (1)/(6) x^{(-2)/(3) }

Final answer:-

Put x=1


g^(l) (1) = (1)/(6) 1^{(-2)/(3) } = (1)/(6)

User Sean Kladek
by
4.7k points